FAKTOR STUNTING PADA BALITA USIA 12-59 BULAN DI UPT. PUSKESMAS GEDUNG SURIAN, LAMPUNG BARAT - Yayang Khomsatun Khoiriah; Yulistiana Evayanti; Ratna Dewi Putri; Dainty Maternity (JKM (Jurnal Kebidanan Malahayati), 2020)
ABSTRACT  Background:  Stunting is a condition of chronic malnutrition that occurred during the critical period of the process of growing and flowers ranging from the fetus.  Stunting cases in West Lampung Regency competed in 3 consecutive years 2015-2017, by the year 2015 the number reached 28.5%, stunting on 2016 reached 33.2% and in the year 2018 rose to 37.3% of the work-area of The Technical Service Unit of Gedung Surian Central Health  with prevalence stuning reached 35.8% in 2018. Purpose:  in this research is to know the factors that relate to a Stunting on Toddler age 12-59 months in The Technical Service Unit of Gedung Surian Central Health, West Lampung.   Method:  The design of this research is a survey technique using the analytic approach of Cross sectional Imaging in applications using statistical data (SPSS).   Result:  Obtained from the processing of data using SPSS applications showed that the factors that led to the occurrence of stunting is;  Birth length with the value P-Value reaches the value of 0.039, Odd-Ratio of 3.7;  Birth weight with value P-Value reach 0.000, Odd-Ratio value of 0.607; and the educational level of the mother with the value P-Value reached 0.005 Odd-Ratio of 5.00 Conclutions: The conclusions are the relationship between birth length, birth weight, and mother's education level with the incidence of stunting in children aged 12-59 months.  Suggesstion: The incidence of stunting can be prevented by providing balanced nutrition during pregnancy and and the role of the health department to support people's knowledge to pay more attention to the nutritional adequacy of children.:  Keywords: Stunting, birth weight, birth length, Mother’s known, a growing toddler.  ABSTRAK  Latar Belakang: Stunting Merupakan kondisi kekurangan gizi kronis yang terjadi pada periode kritis dari proses tumbuh dan kembang mulai dari janin.  Kejadian stunting di Kabupaten Lampung Barat mengalami kenaikan pada 3 tahun berturut-turut 2015-2017, yaitu pada tahun 2015 angka stunting mencapai 28,5%, pada 2016 mencapai 33,2% dan pada tahun 2018 meningkat menjadi 37,3% Wilayah kerja Puskesmas Gedung Surian dengan prevalensi stunting mencapai 35,8% tahun 2018. Tujuan: Tujuan penelitian ini untuk mengetahui Faktor-Faktor yang Berhubungan dengan Stunting pada Balita usia 12-59 Bulan di UPT. Puskesmas Gedung Surian Lampung Barat.   Metode Penelitian: Rancangan penelitian ini adalah survey analitik dengan pendekatan Cross sectional, Populasi balita umur 12-59 bulan dengan risiko stunting sebanyak 500, sampel 84, teknik sampling menggunakan quota sampling, pengumpulan data menggunakan kuesioner dan data sekunder, uji statistik menggunakan Chi-Square.   Hasil: Uji statistik menunjukan faktor yang berhubungan dengan stunting antara lain Panjang badan lahir dengan kejadian stunting nilai (P-Value = 0,039 ; OR = 3.7);  Berat badan lahir nilai (P-Value = 0,000 ; OR = 0,607);  Tingkat pendidikan ibu dengan nilai (P-Value = 0,005 ; OR = 5,00);   Kesimpulan: Simpulan ada hubungan panjang badan lahir, berat badan lahir, dan tingkat pendidikan ibu dengan kejadian stunting pada balita usia 12-59 bulan.  Saran : Kejadian stunting dapat dicegah dengan pemberian gizi seimbang pada masa kehamilan dan dan peran serta dinas kesehatan mendukung pengetahuan masyarakat agar lebih memperhatikan kecukupan gizi balita.   Kata kunci: Stunting, Berat badan lahir, Panjang badan lahir, Tingkat pendidikan ibu, Pertumbuhan balita